2009
DOI: 10.1002/we.371
|View full text |Cite
|
Sign up to set email alerts
|

Deformable trailing edge flaps for modern megawatt wind turbine controllers using strain gauge sensors

Abstract: The present work contains a deformable trailing edge fl ap controller integrated in a numerically simulated modern, variablespeed, pitch-regulated megawatt (MW)-size wind turbine. The aeroservoelastic multi-body code HAWC2 acts as a component in the control loop design. At the core of the proposed controller, all unsteady loads are divided by frequency content. Blade pitching and generator moment react to low-frequency excitations, whereas fl aps deal with high-frequency excitations. The present work should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 17 publications
1
69
0
Order By: Relevance
“…Control System Model for instance, an ideal 5-hole Pitot's tube extending from the blade leading edge [9]. A second sensor location is also investigated, and in this case the measuring point is placed at the`typical' three quarter chord position: ε Aoa,ctrl = ε 3/4 = 0.5.…”
Section: Heave Displacement Control the Heave Control Consists Of A Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Control System Model for instance, an ideal 5-hole Pitot's tube extending from the blade leading edge [9]. A second sensor location is also investigated, and in this case the measuring point is placed at the`typical' three quarter chord position: ε Aoa,ctrl = ε 3/4 = 0.5.…”
Section: Heave Displacement Control the Heave Control Consists Of A Pmentioning
confidence: 99%
“…The aerodynamic forces in the simulations by Buhl et al [6] are computed employing Gaunaa's [12] potential ow model for a thin airfoil section undergoing arbitrary motion and camberline deformation. Andersen et al [8] extends the model to take into account the e ects from uid viscosity and simulations including the interaction with a wind turbine standard control system are presented in Andersen et al [9]. Here, it is concluded that by apply-2 ing an active ap control the blade apwise fatigue load would be reduced up to 48 %, with respect to an HAWT without ap-like deformable trailing edges.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Most of the studies opted for control algorithms based on classic PID methods, applied either to each blade independently [13,14,15,16,17], or to the whole rotor through multi-blade coordinate transformation [18,19]; other investigations have instead applied model based control algorithms, as Linear Quadratic Regulators (LQR) [20], Model Predictive Control (MPC) [12,21], or H ∞ control [9]. The flap control actions respond to the deformation state of the rotor blades; in some cases, rotor sensors are assumed to provide direct measurements of the blade deflection and deflection rate [15,20,22,17], whereas other controllers use measurements of the blade flapwise bending moment, either at selected locations along the span [14,16], or, more simply, at the blade root [19,12,21,10].…”
Section: Introductionmentioning
confidence: 99%
“…The flap control actions respond to the deformation state of the rotor blades; in some cases, rotor sensors are assumed to provide direct measurements of the blade deflection and deflection rate [15,20,22,17], whereas other controllers use measurements of the blade flapwise bending moment, either at selected locations along the span [14,16], or, more simply, at the blade root [19,12,21,10]. Some studies have also investigated flap control algorithms where additional information on the in-flow condition along the blade are provided, for instance, by measurements performed with Pitot's tubes mounted on the blade leading edge [14,12,21].…”
Section: Introductionmentioning
confidence: 99%